2018
DOI: 10.3389/fneur.2018.00112
|View full text |Cite
|
Sign up to set email alerts
|

Recovery from Spatial Neglect with Intra- and Transhemispheric Functional Connectivity Changes in Vestibular and Visual Cortex Areas—A Case Study

Abstract: ObjectiveVestibular signals are involved in higher cortical functions like spatial orientation and its disorders. Vestibular dysfunction contributes, for example, to spatial neglect which can be transiently improved by caloric stimulation. The exact roles and mechanisms of the vestibular and visual systems for the recovery of neglect are not yet known.MethodsResting-state functional connectivity (fc) magnetic resonance imaging was recorded in a patient with hemispatial neglect during the acute phase and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The identification of the CA bundle as a negative contributor in the present study reappraises the controversy on the role of this tract on attentional orienting. It has been recently suggested that improvement of neglect symptoms after caloric stimulation in the acute phase is associated on the one hand with increased functional connectivity between bilateral vestibular cortical areas, the parahippocampal areas and the dorsal CA, and on the other hand to reduced interhemispheric connectivity between the former and the visual cortex (Conrad, Boegle, Ertl, Brandt, & Dieterich, ). These findings highlight the role of a functional network involving the CA and parahippocampal structures in visuospatial attention, probably important for the engagement and modulation of spatial orienting and navigation maps (Best, White, & Minai, ; Rowland, Roudi, Moser, & Moser, ).…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the CA bundle as a negative contributor in the present study reappraises the controversy on the role of this tract on attentional orienting. It has been recently suggested that improvement of neglect symptoms after caloric stimulation in the acute phase is associated on the one hand with increased functional connectivity between bilateral vestibular cortical areas, the parahippocampal areas and the dorsal CA, and on the other hand to reduced interhemispheric connectivity between the former and the visual cortex (Conrad, Boegle, Ertl, Brandt, & Dieterich, ). These findings highlight the role of a functional network involving the CA and parahippocampal structures in visuospatial attention, probably important for the engagement and modulation of spatial orienting and navigation maps (Best, White, & Minai, ; Rowland, Roudi, Moser, & Moser, ).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, with regard to the PS, VN and AHP, there was not only an anatomical coincidence reported between vestibular parameters and these phenomena, but also a functional interaction indicated by the finding that various types of vestibular stimulation (caloric or galvanic) are able to reverse signs of these phenomena temporarily [15–17] Indeed, improvement of neglect after vestibular caloric stimulation in the acute phase was associated with significantly increased intrahemispheric and transhemispheric functional connectivity of vestibular cortex areas (insula, operculum) in both hemispheres, but with a reduced interhemispheric connectivity of the visual cortex [18] This interhemispheric connectivity of the vestibular areas (operculum, hippocampus, dorsal anterior cingulum) was also enhanced in the resting state after recovery from neglect 6 months later. Thus, the assumption that the vestibular system is functionally involved in the generation of these symptoms is compatible with the anatomic correlation in our study and the functional interaction between vestibular stimulation and reversal of these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the hMT+ could be subject to the inhibition by vestibular signals or by the feedback from visual-vestibular integration. Indeed, several past studies have observed mutual inhibition in visual-vestibular integration, 29,75,76 especially when the stimulus from the suppressed modality was weak. This suppression might aim to reduce neural noise from the weak modality and resolve sensory conflict.…”
Section: Discussionmentioning
confidence: 99%